Health literacy and its relationship with quality of life, self-reported chronic diseases and difficulties for accessing health services among older adults (Research, Society and Development, 2022)
Purpose: To investigate possible differences on quality of life, self-reported chronic diseases and difficulties to access health services between older adults with adequate and inadequate between health literacy (HL) Methods: Thirty older adults were assessed, and the following data were collected: years of education, perception of difficulties to access health services, health insurance, falls, self-reported chronic diseases. The Short Test of Functional Health Literacy in Adults (S-TOFHLA) was used to assess HL and the 12-Item Short-Form Health Survey (SF-12) to assess QoL. Data were compared between groups with adequate (n=15) and inadequate (n=15) HL using t-tests for independent samples, Mann-Whitney tests and Fisher Exact test, at a significant level of 5%. Results: There was no between-groups difference regarding years of education and SF-12 mental and physical scores. The group with inadequate HL presented perception of less limitation at work or other activities; perception of less difficulty to access health services; and a higher proportion that reported not knowing if they presented chronic diseases. Final considerations: There was no difference between older adults with adequate and inadequate HL regarding quality of life related to the perceptions of limitations and difficulties due to physical and mental health. However, older adults with inadequate HL seem to present a perception of fewer difficulties at work and for accessing health services, besides lower knowledge about presenting chronic diseases.